King of fish : the thousand-year run of salmon - Montgomery, David R., 1961- (Westview Press, 2003)
This book is an accounting of the natural history of the rise and fall of salmon in England, New England, and the Pacific Northwest--with recommendations for bringing the salmon back. In coming to understand the natural and human forces shaping the rivers and mountains of the Pacific Northwest, geologist David Montgomery learned to see the evolution and near-extinction of the salmon as a story of changing landscapes. An integral part of the region's rivers and seas, the salmon that symbolize the Northwest's natural splendor are now endangered, either gone or threatened with extinction across much of their ancestral range. Montgomery shows how a succession of de facto historical experiments-first in the United Kingdom, then in New England, and now in the Pacific Northwest-followed a similar story in which overfishing and sweeping changes to the landscape rendered the world inhospitable to salmon. In King of fish, Montgomery traces the human impacts on salmon over the last 1000 years and examines the implications for both salmon recovery efforts and the more general problem of human impacts on the natural world. The book concludes with recommendations for reinventing the ways in which we make environmental decisions about land, water, and fish.